2020
DOI: 10.1111/sipr.12072
|View full text |Cite
|
Sign up to set email alerts
|

Teaching as Social Influence: Empowering Teachers to Become Agents of Social Change

Abstract: Teachers carry out a number of roles in the educational system. Their primary role is to help all students develop knowledge and skills, but, most of the time, they take on the role of gatekeepers: They evaluate students and exercise selection on the basis of performance. We analyze the roles of teachers through the lens of the literature on social influence, and put forward the proposal that teaching is a form of social influence. We review existing research on the mechanisms that explain the differential eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 125 publications
(162 reference statements)
0
21
1
Order By: Relevance
“…So that children who are given help shows happiness because of the care of their friends. This is in contrary with the research result stated by (Butera et al, 2021;Ferreira et al, 2020) Social competence owned by people is depends on the teacher about what is taught and how to teach it. Sense of caring and gratitude can indeed be stimulated from the initial mathematics learning activities.…”
Section: Chart 1 Display Datacontrasting
confidence: 83%
“…So that children who are given help shows happiness because of the care of their friends. This is in contrary with the research result stated by (Butera et al, 2021;Ferreira et al, 2020) Social competence owned by people is depends on the teacher about what is taught and how to teach it. Sense of caring and gratitude can indeed be stimulated from the initial mathematics learning activities.…”
Section: Chart 1 Display Datacontrasting
confidence: 83%
“…Differences in access to high‐quality schools (Allen, Mian, & Sims, 2016; Burgess, Greaves, & Vignoles, 2020), adequate housing (Equality Trust, 2016; Krivo & Kaufman, 2004; Ofsted, 2013), private tuition (Jerrim, 2017), and healthy nutrition (Ofsted, 2013; Wilder Research, 2014)—to name just a few factors—all contribute substantially to attainment gaps and other educational inequalities. Furthermore, institutional biases that discriminate against certain groups of students also contribute to inequalities in educational outcomes, most notably through biases that manifest in academic tracking allocations, academic assessment and disciplinary practices, and expectations about the behavior and academic performance of different groups (Butera, Batruch, Autin, Mugny, & Quiamzade, 2021). We explore these biases later in this paper.…”
Section: Psychological Barriers Contribute To Educational Inequalitiesmentioning
confidence: 99%
“…Nevertheless, cooperative learning does not automatically lead to improved learning. The educational system, notwithstanding its formative mission, is fundamentally competitive [23,24], especially in the neo-liberal ideology in which most Western societies and educational institutions are embedded [25,26], and it is possible that this competitive atmosphere interferes with the effects of cooperative learning [27,28]. Indeed, a line of research carried out with university students has shown that focus on social comparison with a partner during cooperative learning may lead to a dual effect of partner's competence [29].…”
Section: Introductionmentioning
confidence: 99%